2022
DOI: 10.5217/ir.2020.00156
|View full text |Cite
|
Sign up to set email alerts
|

Management of inflammatory bowel disease in the COVID-19 era

Abstract: To date, there are limited data regarding IBD and COVID-19, but evidence with a higher quality has been gradually accumulated recently. We aimed to review the management of IBD in the COVID-19 era. RISK OF COVID-19 IN IBD PATIENTSIn addition to fever and respiratory symptoms, 8 about 15% of COVID-19 patients complain of gastrointestinal symptoms such as diarrhea, nausea, vomiting, and anorexia, with variable frequencies. 9 These symptoms are more likely to be noted in patients with severe This could be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Although there are still limited data on the safety of IBD drugs, all experts and societies recommend continuing IBD-specific treatment since it has been recognized that the risk of active disease is higher than the uncertain risk of immunosuppression, which tends to increase the risk of COVID-19. 8,[19][20][21] Although early data have reported that combination therapy and thiopurine monotherapy may be associated with a higher risk of severe COVID-19 infection in IBD patients, 22 supporting evidence regarding the discontinuation of thiopurine in patients on stable maintenance is still very weak. 19,20 Considering that only 7% of patients discussed the safety of their drugs with medical staff, we also need to pay attention to the effect of the lack of communication between patients and the medical staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are still limited data on the safety of IBD drugs, all experts and societies recommend continuing IBD-specific treatment since it has been recognized that the risk of active disease is higher than the uncertain risk of immunosuppression, which tends to increase the risk of COVID-19. 8,[19][20][21] Although early data have reported that combination therapy and thiopurine monotherapy may be associated with a higher risk of severe COVID-19 infection in IBD patients, 22 supporting evidence regarding the discontinuation of thiopurine in patients on stable maintenance is still very weak. 19,20 Considering that only 7% of patients discussed the safety of their drugs with medical staff, we also need to pay attention to the effect of the lack of communication between patients and the medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…8,[19][20][21] Although early data have reported that combination therapy and thiopurine monotherapy may be associated with a higher risk of severe COVID-19 infection in IBD patients, 22 supporting evidence regarding the discontinuation of thiopurine in patients on stable maintenance is still very weak. 19,20 Considering that only 7% of patients discussed the safety of their drugs with medical staff, we also need to pay attention to the effect of the lack of communication between patients and the medical staff. Neglecting treatment due to misinformation can exacerbate IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The precautions that should be taken for steroid therapy could be minimize their use, avoid starting new therapies, and taper down the dose if it is higher than 20 mg/day of prednisolone or equivalent, always taking into account the disease activity. In case of acute, severe form of UC, corticosteroid treatment could be started after urgent molecular swab or after excluding COVID-like symptoms [ 9 ].…”
Section: Drugs and Inflammatory Bowel Diseases: What Have We Learned?mentioning
confidence: 99%
“…In these patients, there is also an increased expression of ACE2 in the gut mucosa [ 7 ] and an increase of ACE2 serum levels (as well as Ang1–7 and the ACE2: ACE ratio) [ 8 ]. This could play a protective role in the blood [ 9 ] by acting as a competitive receptor for the virus and thus leading to the reduction of the viral load that would infect the host.…”
Section: Introductionmentioning
confidence: 99%
“… 5 6 Patients with IBD are reported to be at no greater risk of contracting COVID-19 than the general population. 7 8 There have been no confirmed cases of IBD patients with confirmed COVID-19 in Korea yet. This case series reports on COVID-19 confirmed IBD patients' clinical features and characteristics in Korea.…”
mentioning
confidence: 99%